Error function approximations of interest in electrochemistry. - Magnani, R.; Daun, G.; Benedetti, Assis Vicente [UNESP] (Editora Unesp, 1996)
The error function is present in several equations describing eletrode processes. But, only approximations of this function are used. In this work, these and other approximations are studied and evaluated according to precision.
Keywords: error function; power-series expansion; chronoamperometry